Mining environmental liabilities, health and agriculture: a first spatial approach - Carlos Orihuela, José (2017)
The international economic development literature abounds with studies on national and local impacts of extractive activities on employment and income. However, studies on negative externalities such as pollution are rare. Using an administrative database on mining environmental liabilities (MAPs) and geo-referenced household surveys, we explore how proximity to these liabilities affects health conditions and agricultural production in Peruvian households in 2016. First, we obtain partially robust evidence to spatial correlation of the relationship between relative proximity to a MAP and health indicators: children with lower height and weight, according to age, and with higher probability of being malnourished. Second, we obtain evidence that proximity to a MAP is related to a lower number of livestock in farming households.